From CGIAR Research to Action: Strengthening Science-Policy Linkages - Nandi, Ravi (CIMMYT, 2025)
CGIAR is strengthening the link between research and policy by promoting simplified, impactful science communication and strategic engagement with policymakers to drive sustainable, evidence-based agricultural innovation